Phosphorus Fertilization Enhances Productivity of Forage Corn (Zea mays L.) Irrigated with Saline Water - Hamza Bouras; Ahmed Bouaziz; Redouane Choukr-Allah; Abdelaziz Hirich; Krishna Prasad Devkota; Bassou Bouazzama (Plants, 2021)
Salinity is a major problem affecting crop production in many regions in the world including Morocco. Agricultural practices such as fertilization could be useful to overcome this problem and improve crop productivity. The objective of our study was to evaluate the combined effect of phosphorus fertilization and irrigation water salinity on growth, yield, and stomatal conductance of forage corn (Zea mays L.) cv. “Sy sincerro”. Field experiments were carried out for two years testing four levels of irrigation water salinity (ECw = 0.7; 2, 4, and 6 dS·m−1) and three rates of phosphorus (105, 126, and 150 kg P2O5·ha−1) fertilization conducted in a split-plot design with three replications. The obtained results show that irrigation water salinity had a negative effect on all monitored parameters. For instance, the dry matter yield reduced by an average of 19.3 and 25.1% compared to the control under saline irrigation with an EC value equal to 4 and 6 dS·m−1, respectively. The finding also showed that phosphorus applications tend to increase root weight, root length, stem length, leaf stomatal conductance, grain yield and dry matter yield under salinity conditions. For example, the addition of phosphorus with a rate of 126 and 150 kg P2O5·ha−1 respectively improved dry matter yield by an average of 4 and 9% under low salinity level (ECw = 2 dS·m−1), by 4 and 15% under medium salinity (4 dS·m−1), and by 6 and 8% under a high salinity level (6 dS·m−1). Our finding suggests that supplementary P application could be one of the best practices to reduce the adverse effects of high salinity on growth and development of forage corn.